Comportamento de frangos de corte em diferentes condições térmicas - Klein, Daniela Regina (2016)
The climate changes are a challenge to maintain the production of broiler, and find a balance between the costs of maintaining the proper temperature and optimize production. The aim of this study was to evaluate broiler behavior in three different thermal conditions: comfort, cold and heat, analyzing the behavior and production performance. The experiment was conducted in three climatic chambers, and monitored by video cameras. Each week were used 27 birds, divided between the chambers and individually identified. The experiment period was: 3rd, 4th, 5th and 6th week of age from broilers. The birds remained housed in the chamber for five days, 48 hours of adaptation and 72 hours to collect data. Each compartment of the chamber provides a different temperature: comfort (recommendation strain), low (8 °C below the comfort) and high (8 °C above the comfort) simulating conventional housing conditions. To evaluate the broiler behavior were analyzed 15 minutes of video every 3 hours, and the performance data. The experimental design was completely randomized with variance analysis and Tukey test at 5%. The behaviors were evaluated too with data mining, using thermal conditions class, applying J48 algorithm. The broiler behaviors were efficient to maintain productivity in short-term stress conditions. With data mining was possible to establish behavior standards applicable to thermal condition indicators of broilers. These are important knowledge for the sustainability of broilers production, helping in decision making for mitigation measures.